Global Trends in Innovation and Evaluation of 21st Century Physics Learning: A Bibliometric and Systematic Review - Hawur, Proki Karandja; Supahar; Rasyid, Fauziah; Gunawan, Cahya Widya (Kasuari: Physics Education Journal (KPEJ), 2025)
Physics education in the 21st century is undergoing various innovations to enhance its effectiveness and relevance in the digital era. This study aims to map current research trends in high school physics education through bibliometric analysis and SLR analysis methods on articles indexed in the Scopus database. This study utilized 62 articles on physics learning that were analyzed. The study results show that innovations in physics learning include the use of simulations and virtual reality, digital applications such as Getsmart and PhET, project-based learning (PBL) approaches, as well as the use of digital tools like Tinkercad and Arduino Uno. In addition, STEM-based learning approaches, flipped classrooms, and hybrid learning are increasingly being implemented to enhance 21st-century skills such as critical thinking, problem-solving, and creativity. This study also found that teacher training adopting the Nature of Science (NOS) approach and technology in teaching contributes to the improvement of pedagogical competence. Learning evaluations using HOTS-based instruments and technology-based e-assessments have proven effective in measuring students' understanding and interest in physics.